# Difference between revisions of "Foldl as foldr"

(foldl using Update monoid) |
(foldlMaybeMonoid) |
||

Line 51: | Line 51: | ||

By the way: |
By the way: |
||

+ | <hask>Update a</hask> is just <hask>Dual (Endo a)</hask>. |
||

If you use a <hask>State</hask> monad instead of a monoid, |
If you use a <hask>State</hask> monad instead of a monoid, |
||

you obtain an alternative implementation of <hask>mapAccumL</hask>. |
you obtain an alternative implementation of <hask>mapAccumL</hask>. |
||

Line 58: | Line 59: | ||

The answer to the second question is: |
The answer to the second question is: |
||

⚫ | |||

+ | Using the <hask>foldr</hask> expression we can write variants of <hask>foldl</hask> |
||

+ | that behave slightly different from the original one. |
||

⚫ | |||

and thus may also terminate on infinite input. |
and thus may also terminate on infinite input. |
||

The function <hask>foldlMaybe</hask> terminates with <hask>Nothing</hask> as result |
The function <hask>foldlMaybe</hask> terminates with <hask>Nothing</hask> as result |
||

Line 68: | Line 71: | ||

</haskell> |
</haskell> |
||

+ | Maybe the monoidic version is easier to understand. |
||

+ | The implementation of the fold is actually the same, we do only use a different monoid. |
||

+ | <haskell> |
||

+ | import Control.Monad ((>=>), ) |
||

+ | |||

+ | newtype UpdateMaybe a = UpdateMaybe {evalUpdateMaybe :: a -> Maybe a} |
||

+ | |||

+ | instance Monoid (UpdateMaybe a) where |
||

+ | mempty = UpdateMaybe Just |
||

+ | mappend (UpdateMaybe x) (UpdateMaybe y) = UpdateMaybe (x>=>y) |
||

+ | |||

+ | foldlMaybeMonoid :: (a -> b -> Maybe a) -> a -> [b] -> Maybe a |
||

+ | foldlMaybeMonoid f a bs = |
||

+ | flip evalUpdateMaybe a $ |
||

+ | mconcat $ |
||

+ | map (UpdateMaybe . flip f) bs |
||

+ | </haskell> |
||

[[Category:Idioms]] |
[[Category:Idioms]] |

## Revision as of 23:12, 16 February 2009

When you wonder whether to choose foldl or foldr you may remember,
that both `foldl`

and `foldl'`

can be expressed as `foldr`

.
(`foldr`

may lean so far right it came back left again.)
The converse is not true, since `foldr`

may work on infinite lists,
which `foldl`

variants never can do.
It holds

```
foldl :: (a -> b -> a) -> a -> [b] -> a
foldl f a bs =
foldr (\b g x -> g (f x b)) id bs a
```

Now the question are:

- How can someone find a convolved expression like this?
- How can we benefit from this rewrite?

## Folding by concatenating updates

Instead of thinking in terms of `foldr`

and a function `g`

as argument to the accumulator function,
I find it easier to imagine a fold as a sequence of updates.
An update is a function mapping from an old value to an updated new value.

```
newtype Update a = Update {evalUpdate :: a -> a}
```

We need a way to assemble several updates.
To this end we define a `Monoid`

instance.

```
instance Monoid (Update a) where
mempty = Update id
mappend (Update x) (Update y) = Update (y.x)
```

Now left-folding is straight-forward.

```
foldlMonoid :: (a -> b -> a) -> a -> [b] -> a
foldlMonoid f a bs =
flip evalUpdate a $
mconcat $
map (Update . flip f) bs
```

Now, where is the `foldr`

?
It is hidden in `mconcat`

.

```
mconcat :: Monoid a => [a] -> a
mconcat = foldr mappend mempty
```

Since `mappend`

must be associative
(and is actually associative for our `Update`

monoid),
`mconcat`

could also be written as `foldl`

,
but this is avoided, precisely `foldl`

fails on infinite lists.

By the way:
`Update a`

is just `Dual (Endo a)`

.
If you use a `State`

monad instead of a monoid,
you obtain an alternative implementation of `mapAccumL`

.

## foldl which may terminate early

The answer to the second question is:
Using the `foldr`

expression we can write variants of `foldl`

that behave slightly different from the original one.
E.g. we can write a `foldl`

that can stop before reaching the end of the input list
and thus may also terminate on infinite input.
The function `foldlMaybe`

terminates with `Nothing`

as result
when it encounters a `Nothing`

as interim accumulator result.

```
foldlMaybe :: (a -> b -> Maybe a) -> a -> [b] -> Maybe a
foldlMaybe f a bs =
foldr (\b g x -> f x b >>= g) Just bs a
```

Maybe the monoidic version is easier to understand. The implementation of the fold is actually the same, we do only use a different monoid.

```
import Control.Monad ((>=>), )
newtype UpdateMaybe a = UpdateMaybe {evalUpdateMaybe :: a -> Maybe a}
instance Monoid (UpdateMaybe a) where
mempty = UpdateMaybe Just
mappend (UpdateMaybe x) (UpdateMaybe y) = UpdateMaybe (x>=>y)
foldlMaybeMonoid :: (a -> b -> Maybe a) -> a -> [b] -> Maybe a
foldlMaybeMonoid f a bs =
flip evalUpdateMaybe a $
mconcat $
map (UpdateMaybe . flip f) bs
```